Religiosity as a Coping Mechanism for Burnout: A Case Study of Women Experiencing Fatherlessness - Rahmadani Mardhoti (Jurnal Psikologi Terapan, 2025)
This study examines the function of religiosity as a coping strategy for burnout in women who have experienced fatherlessness. Fatherlessness, characterized by the lack of a paternal figure either physically or emotionally, has been linked to heightened susceptibility to psychological distress, encompassing identity confusion, emotional instability, and burnout. A qualitative case study methodology was employed to gather data from two Muslim women aged 18–25 through comprehensive online interviews conducted via Google Meet. The data were subjected to thematic analysis to discern persistent patterns associated with religiosity and coping behavior. The results showed five main themes: (1) losing a father figure as a cause of burnout, (2) changes in identity and emotional dynamics after loss, (3) withdrawal as a first way to deal with loss, (4) religiosity as a way to deal with emotions and spirituality, and (5) crisis and spiritual acceptance. The findings suggest that religiosity serves a transformative function in assisting individuals to cope with burnout and emotional turmoil. Religious practices, including prayer, supplication, and Qur’anic reflection, offered emotional solace, a sense of connection, and a framework for meaning-making that culminated in acceptance and gratitude. The research concludes that religiosity functions as an emotional regulator and a source of psychological resilience for fatherless women, aiding their transition from emotional distress to spiritual tranquility. These findings emphasize the necessity of incorporating spiritual dimensions into psychological support and counseling interventions for individuals facing analogous conditions.